2020
DOI: 10.1007/s41669-020-00196-w
|View full text |Cite
|
Sign up to set email alerts
|

Self-Monitoring and Management of Blood Pressure in Patients with Stroke or TIA: An Economic Evaluation of TEST-BP, A Randomised Controlled Trial

Abstract: Background Prevention of secondary stroke following initial ictus is an important focus of after-stroke care. Blood pressure (BP) is a key risk factor, so usual care following stroke or transient ischaemic attack includes regular BP checks and monitoring of anti-hypertensive medication. This is traditionally carried out in primary care, but the evidence supporting self-monitoring and self-guided management of BP in the general population with hypertension is growing. Objective Our objective was to estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The majority of studies were excluded because they were not full economic evaluations (see Appendix 2). Two further 49,50 studies were identified from weekly auto-alerts and the full texts of these studies were obtained. However, both studies 49,50 were excluded as they were not primary prevention studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies were excluded because they were not full economic evaluations (see Appendix 2). Two further 49,50 studies were identified from weekly auto-alerts and the full texts of these studies were obtained. However, both studies 49,50 were excluded as they were not primary prevention studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two further 49,50 studies were identified from weekly auto-alerts and the full texts of these studies were obtained. However, both studies 49,50 were excluded as they were not primary prevention studies. Eight studies [51][52][53][54][55][56][57][58] met the inclusion criteria of this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Sharing disease knowledge with patients and maintaining interactive guidance with them through the Internet platform greatly stimulate patients' active compliance behaviour, which can effectively improve patients' medication compliance (Zhu et al, 2015). In recent years, evidence supporting that the use of blood pressure self-monitoring in the general population with stroke reduces the risk of recurrence and the financial burden of healthcare has been growing (Doogue et al, 2023;Kim et al, 2020;Schwartz et al, 2018). Therefore, further study should focus on blood pressure self-monitoring during the transition process.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research has suggested that self-management education (e.g., life management, sports management, treatment compliance management, and psychosocial factor management) can enhance the self-efficacy of stroke patients at the recovery stage. Patients can maintain and promote their health, reduce the effect of diseases, and firmly cope with their diseases ( Liu, 2019 ; Kim et al, 2020 ; He et al, 2022 ). The higher the self-management level of patients, the better the treatment compliance and the better the rehabilitation effect will be ( Gao et al, 2014a ; Dong et al, 2018 ; Shi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%